Genetic polymorphisms in genes of class switch recombination and multiple myeloma risk and survival: an IMMEnSE study - Campa, Daniele; Raab, Marc-Steffen; Huhn, Stefanie; Merz, Maximilian; Schöttker, Ben; Goldschmidt, Hartmut; Brenner, Hermann (Leukemia and lymphoma, 2019)
Genetic variants in genes acting during the maturation process of immature B-cell to differentiated plasma cell could influence the risk of developing multiple myeloma (MM). During B-cell maturation, several programmed genetic rearrangements occur to increase the variation of the immunoglobulin chains. Class switch recombination (CSR) is one of the most important among these mechanisms. Germline polymorphisms altering even subtly this process could play a role in the etiology and outcome of MM. We performed an association study of 30 genetic variants in the key CSR genes, using 2632 MM patients and 2848 controls from the International Multiple Myeloma rESEarch (IMMEnSE) consortium, the Heidelberg MM Group and the ESTHER cohort. We found an association between LIG4-rs1555902 and decreased MM risk, which approached statistical significance, as well as significant associations between AICDA-rs3794318 and better outcome. Our results add to our knowledge on the genetic component of MM risk and survival.
Gesehen am 14.08.2019